АНАЛІЗ НЕСИМЕТРИЧНИХ РЕЖИМІВ У ШЕСТИЕЛЕКТРОДНШ ДУГОВІЙ ЕЛЕКТРОПЕЧІ ІМПУЛЬСНОГО СТРУМУ - Гудим , В.; Дроздовскі, П.; Постолюк, А. (Інститут електродинаміки НАН України, Київ, 2012)
In six of the electrode for electric arc furnace pulsating current pu-order mathematical modeling studied mode coordinates and the energy characteristics of the most likely not symmetric modes of electric arc furnace. References 2, figure 1.